Implementación de un sistema automático de llenado de botellas para la empresa Spring Water. - Llanqui Gavilanes, Byron Leonardo (2022)
The company Spring Water's main activity is the industrialization of bottling water, this market segment has increased its demand every year, however the low quality and reaction to customer requirements by the industries are slowing down growth, for this reason, this company, with the objective of being competitive in the market, detects the need to modernize its manufacturing processes, focused on improving quality and increasing production volume. This project was created to solve the problem presented with the implementation of an automated system for the water bottling process, where an electro-mechanical system was designed with technical and demographic research, which allows achieving the required results. The implementation of the automatic system allows operators to become more technical, reduce unnecessary efforts, reduce manufacturing times, reduce costs, control filling quantities, guaranteeing the customer quality in the final product.